Introduction to Snake Wells with particular focus on Rotary Steerable System - Prabha, Aditya; Mangwani, Kartik; Singh, Manpreet (Journal of Advanced Research in Petroleum Technology & Management, 2021)
The snake well drill is a path breaking technology that permits us to extract oil from the previously inaccessible places. In contrast with conventional drills, advanced software grants the snake well drill to trail intricate horizontal paths, cutting through shale and sand to reach numerous of diverse reservoir pockets from a single drilling platform. Snake Wells use a blend of technologies comprising extended reach drilling, swellable wellbore packers and remotely operated zonal isolation and control. Swellable wellbore packer is a segregation device that depends on elastomers to swell and form an annular seal when immersed in certain wellbore fluids. The directional drilling technique consents the path of the well to be rapt to achieve contact with as many potentially producing features as possible. This results in a ‘snake like’ well path which intertwines up and down through multiple geological features in order to accomplish utmost reservoir drainage. It uses mobile drilling units which dodges dismantling and reassembling drilling equipment for each pad, making the process swifter and conserving resources. Furthermore, snake wells encompass advanced directional drilling practices viz. steerable drill bits and software that generates comprehensive models of underground geology. This enables drillers to hit production targets that are less than 2 m across and miles below the surface. The pipe that maneuvers oil drills is supple enough to snake around to reach secluded pockets or follow a reservoir that meanders across the terrain. This is a comprehensive study which ushers diverse technologies incorporated in Snake wells with a distinct emphasis on Rotatory Steerable System utilized in mobile drilling units which proliferates well connectivity and in turn enhances production.